Experimental and Theoretical Studies of Eosin Y Dye as Corrosion Inhibitors for Carbon Steel in Perchloric Acid Solution - Tarik Attar; Abbes Benchadli; Boulanouar Messaoudi; Esma Choukchou-Braham; Naceur Benhadria (Bulletin of Chemical Reaction Engineering & Catalysis, 2020)
The adsorption behavior and the inhibition performance of Eosin Y Dye for carbon steel corrosion in 1 M perchloric acid solution have been carried using weight loss and scanning electron micrograph (SEM) techniques as well theoretical calculations based on density functional theory (DFT). The studied inhibitor concentrations were between 5´10-5 M and 5´10-3 M. Results obtained revealed that Eosin Y is an effective inhibitor and its inhibition efficiency increases with increasing concentration to attain 96.91% at 5´10-3 M at 30 °C. Thermodynamic parameters such as adsorption heat, adsorption entropy and adsorption free energy were obtained from experimental data of the temperature studies of the inhibition process at five temperatures ranging from 20 to 60 °C. It was found that the adsorption of Eosin Y could prevent steel from weight loss and the adsorption accorded with the Langmuir adsorption isotherm. The free energy of adsorption showed that the corrosion inhibition takes place by spontaneous physicochemical adsorption of inhibitor molecules on the carbon steel surface. SEM and DFT studies confirm the adsorption of Eosin Y on carbon steel surface. Copyright © 2020 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).